Development of Writing Materials for Writing Essay Based on Religious Integrated Neuroscience in Elementary School - Nur Rahma Kasim (IAIN Palopo, 2020)
The main problem in this research is to find out the design of valid teaching materials and the practicality of teaching materials. This research is a Research & Development (R&D) research method. To develop the product, this research uses a 4-D development model consisting of four stages, namely: (1) the defined phase, (2) the design phase, (3) the development phase, and (4) the disseminate stage. This research was conducted in class V of SD Negeri 1 Lalebbata Palopo, which acted as the subject of the study was the fifth-grade students totaling 25 people. Data collection techniques in this study are: observation, documentation, Questionnaire, and Validation. Analysis of the data used by the researcher was to test its validity by using the Aiken's formula and for analyzing student questionnaire response data and observations using descriptive statistical analysis. The results of this study indicate that the integrated religious neuroscience-based teaching material is said to be valid by three validators with several revisions so that it can be said to be valid and can be tested, then this teaching material can be said to be interesting because the results from the questionnaire responses of 20 students tend to agree with teaching material developed. Thus this research needs to be socialized so that it can become a consideration of teachers in schools in improving students' writing skills.